Quantitative 3d Integration Of Electromagnetic And Seismic Data To Optimize Structural Similarity Inversion Results In Offshore Northwest Borneo, Malaysia - Saleh, Ahmad Shahir (2023)
Three-dimensional (3D) inverse modelling of seismic and electromagnetic (EM) geophysical data coupled by the cross-gradient criterion is well known to maximize accuracy and reduce uncertainty in subsurface exploration but this requires solving a large-size inverse problem by regularization methods whose optimization is not fully understood and require further research. This study investigated the optimization of 3D regularized inversion using seismic, controlled source EM (CSEM), magnetotelluric (MT) and well data from offshore northwest Borneo. The effect of regularization was studied by performing several inversions of realistic synthetic 3D MT data. Using the best regularization weight found, the optimal cross-gradient weight was found by comparing 3D MT inversion results against the available resistivity well logs for several trial weights. Interpolation of resistivity logs with seismic velocity as secondary guide was found to be the best approach for building the initial resistivity model. The optimized seismic-guided MT inversion was found to produce a more geologically plausible model as compared to the model from the conventional approach. Finally, 3D anisotropic joint CSEM-MT inversion and seismic inversion were conducted. A new attribute termed the seismic-EM projection (SEMP) was defined to further qualify potential reservoirs based on elastic properties and resistivity values. To avoid the risk of encountering tight brine reservoir, the extended elastic impedance (EEI) approach was used to predict total porosity in 3D. The SEMP and EEI attributes have highlighted several geobodies with hydrocarbon potential.